OPTICAL FEATURES OF AG/AU-WO3-X PLASMONIC COMPOSITE THIN FILMS - Mukhametkarimov, Yerzhan; Gusseinov, Nazim; Nemkayeva, Renata; Dosseke, Ulantay; Aitzhanov, Madi (National Laboratory Astana, 2022)
In this work, plasmonic composite thin films based on tungsten oxide (WO3) matrix and Ag/Au nanoparticles (NPs) were deposited by RF magnetron sputtering. As deposited thin films have amorphous substoichiometric WO3-x matrices with isolated noble metal NPs with average sizes of about ~3 nm.
Keywords: Type of access: Embargo; Tungsten oxide; plasmonic composite thin films